2000
DOI: 10.1074/jbc.275.8.5472
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Peptide-binding Site in the Heat Shock Chaperone/Tumor Rejection Antigen gp96 (Grp94)

Abstract: Heat shock protein (HSP)-peptide complexes from tumor cells elicit specific protective immunity when injected into inbred mice bearing the same specific type of tumor. The HSP-mediated specific immunogenicity also occurs with virus-infected cells. The immune response is solely due to endogenous peptides noncovalently bound to HSP. A vesicular stomatitis virus capsid-derived peptide ligand bearing a photoreactive azido group was specifically bound by and cross-linked to murine HSP glycoprotein (gp) 96. The pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 39 publications
(7 reference statements)
4
75
1
Order By: Relevance
“…It was reported that both the N-and C-terminal fragments of gp96 are able to bind peptides (22,23), with the N-terminal fragment behaving at a similar capacity as the full-length gp96 (19). However, whether the terminal fragments can serve as an adjuvant as effectively as the full-length gp96 remains to be determined.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that both the N-and C-terminal fragments of gp96 are able to bind peptides (22,23), with the N-terminal fragment behaving at a similar capacity as the full-length gp96 (19). However, whether the terminal fragments can serve as an adjuvant as effectively as the full-length gp96 remains to be determined.…”
mentioning
confidence: 98%
“…It was reported that gp96 might contain a peptidebinding element within its N-and C-terminal domains (22,23), but whether the peptide binding domains can generate immune effects is not known. To address this issue, two terminal fragments of gp96, N333 (22-355 aa) and C190 (561-751 aa), were cloned into pGEX-6p1 expression vector, expressed in bacteria, and purified on a gel filtration column after removing GST as described in Materials and Methods (Fig.…”
Section: Preparation Of Hsp Gp96 and Its Terminal Fragmentsmentioning
confidence: 99%
“…Both the putative N-terminal domain and the acidic domain are required for binding of nucleotides and inhibitors to GRP94 (15). A peptide-binding site was defined within the C-terminal domain of GRP94 by cross-linking pyrene-modified VSV8 (16,17), an octapeptide known to be presented via GRP94 to T cells (3). This site, centered around amino acids 624 -630, was modeled as a shallow surface groove formed by ␣ helices, resembling the peptide-binding site of a major histocompatibility locus protein (16).…”
mentioning
confidence: 99%
“…A peptide-binding site was defined within the C-terminal domain of GRP94 by cross-linking pyrene-modified VSV8 (16,17), an octapeptide known to be presented via GRP94 to T cells (3). This site, centered around amino acids 624 -630, was modeled as a shallow surface groove formed by ␣ helices, resembling the peptide-binding site of a major histocompatibility locus protein (16). Site-directed mutations showed that VSV8 binding to this site is dependent on aromatic side chains for binding affinity (17).…”
mentioning
confidence: 99%
“…Those of us who know the protein as gp96 will be more familiar with its high-affinity peptide binding properties (Li and Srivastava, 1993) and its potential role as an accessory molecule in loading antigens onto MHC class I molecules in the ER. Gp96 has a peptide binding site located in a conserved region of the protein between amino acids 624 and 630 (Linderoth et al, 2000). Studies have now shown that cellular peptide-gp96 complexes, probably derived from dying, infected cells, are taken up by antigen-presenting cells.…”
Section: Gp96/grp94mentioning
confidence: 99%